2016
DOI: 10.1186/s12913-016-1333-6
|View full text |Cite
|
Sign up to set email alerts
|

How do case managers spend time on their functions and activities?

Abstract: BackgroundCase management has been a widely accepted approach to practice in various care settings. This study aimed to explore how community aged care case managers allocated their time to case management functions, how frequently they performed specific case management activities, and what factors influenced the frequency of their activities.MethodsThe study involved 154 survey participants, or 17.1 % of the target case managers in the State of Victoria, Australia. Key information collected included particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
(34 reference statements)
0
9
0
2
Order By: Relevance
“…This study showed that care need levels did not significantly influence case management performance. Only a few client factors (such as having high care needs and having carers) were significantly associated with the frequency ratings of activities (7). Also, this study (7) showed that a lack of community resources and a lack of communication with surrounding people need not be related to performance at all steps (see (16) for the Japanese experience).…”
Section: Sex Of Clientsmentioning
confidence: 77%
See 3 more Smart Citations
“…This study showed that care need levels did not significantly influence case management performance. Only a few client factors (such as having high care needs and having carers) were significantly associated with the frequency ratings of activities (7). Also, this study (7) showed that a lack of community resources and a lack of communication with surrounding people need not be related to performance at all steps (see (16) for the Japanese experience).…”
Section: Sex Of Clientsmentioning
confidence: 77%
“…Only a few client factors (such as having high care needs and having carers) were significantly associated with the frequency ratings of activities (7). Also, this study (7) showed that a lack of community resources and a lack of communication with surrounding people need not be related to performance at all steps (see (16) for the Japanese experience). The reasons why patient factors, community resources or communication with stakeholders did not have a significant influence on CMs' performance may be related to their behavior when influenced by work overload.…”
Section: Sex Of Clientsmentioning
confidence: 77%
See 2 more Smart Citations
“…Notably, accountability obligations may be more extensive than the degree of autonomy that professionals are permitted to exercise [ 32 ]. Furthermore, the care-managers make decisions that affect client outcome and overall system resources [ 33 ], while decision-making is influenced by the collective wisdom of the team, the role of family and the messiness of the process [ 34 ]. There is a tension and ambiguity that influences care-managers’ working conditions, thus contributing to increased stress levels and resultant staffing problems and affecting the quality of service given to older people in particular [ 35 ].…”
Section: Introductionmentioning
confidence: 99%